THE IMPORTANCE OF PROTECTION METHODS AGAINST PUCCINIA STRIIFORMIS AND ERYSIPHE GRAMINIS F. SPTRITICI ON WHEAT AND THEIR OUTCOME ON GRAIN STRUCTURE AND THE SIGNIFICANCE OF CHEMICAL ACTIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, the effect of drugs used against Puccinia striiformis and Erysiphe graminis f.sptritici in the fields of the foothills of Kashkadarya region on grain quality was 707.6-720.6 g/l on average in the case of fungicide etolon. It was determined that the average of 793.6-799.1 g/l that was higher in the variant used in fungicide +suspension than fungicide itself.